A review on the applications of virtual reality, augmented reality and mixed reality in surgical simulation: an extension to different kinds of surgery. (2nd January 2021) - Lungu, Abel J; Swinkels, Wout; Claesen, Luc; Tu, Puxun; Egger, Jan; Chen, Xiaojun
ABSTRACT: Background : Research proves that the apprenticeship model, which is the gold standard for training surgical residents, is obsolete. For that reason, there is a continuing effort toward the development of high-fidelity surgical simulators to replace the apprenticeship model. Applying Virtual Reality Augmented Reality (AR) and Mixed Reality (MR) in surgical simulators increases the fidelity, level of immersion and overall experience of these simulators. Areas covered : The objective of this review is to provide a comprehensive overview of the application of VR, AR and MR for distinct surgical disciplines, including maxillofacial surgery and neurosurgery. The current developments in these areas, as well as potential future directions, are discussed. Expert opinion : The key components for incorporating VR into surgical simulators are visual and haptic rendering. These components ensure that the user is completely immersed in the virtual environment and can interact in the same way as in the physical world. The key components for the application of AR and MR into surgical simulators include the tracking system as well as the visual rendering. The advantages of these surgical simulators are the ability to perform user evaluations and increase the training frequency of surgical residents.